Convergent structure of multitrophic communities over three continents. (18th October 2013) - Segar, Simon T.; Pereira, Rodrigo A. S.; Compton, Steve G.; Cook, James M.
Astract: Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75MYA, do not show long‐term 'inheritance' of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.